Fifty years of goose research and conservation by The Wildfowl & Wetlands Trust - Mitchell, Carl; Boyd, Hugh; Owen, Myrfyn; Ogilvie, Malcolm (Wildfowl, 1996)
The Wildfowl & Wetlands Trust (WWT) pioneered goose counting and research in the UK and has contributed to the conservation of goose species by establishing reserves for the birds in winter. This paper describes the development of the goose monitoring schemes, largely carried out by volunteer counters, that underpin our understanding of the distribution, abundance and dynamics of our goose populations. The diverse range of investigations WWT has undertaken on geese in the last 50 years is described, and the value of long-term population studies discussed. The importance of international collaboration for the effective conservation of migratory wildfowl is emphasized.